An interrogation into the influence of patriarchy on the representation of women in Zimbabwean films: the case of Daves Guzha’s “sinners” and Tsitsi Dangarembga’s i want a wedding dress - Munetsi, Pamela Tsitsi (Midlands State University, 2017)
Film is a potent tool of communication with a large potential to cement or unsettle social relationships. The study focused on an interrogation into the influence of patriarchy to the representation of women in Zimbabwean films. Sinners by Daves Guzha and I want a wedding dress by Tsitsi Dangarembga were analysed. A qualitative research approach was done to ascertain whether such influence on the representation empowers or disempowers women. The study also examined the possible impacts of such representations on women on the audience/consumers of such films. Interviews with the audience were also done and results revealed that most Zimbabwean films celebrates negative stereotypes of women. Recommendations made are that filmmakers should create images that are gender neutral, images that empower both men and women in the society. Women filmmakers should also stop taking roles that negatively represent them in films.